Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

In simplifying $$[3a(b-c)+5][-3a(b-c)-5],$$ I used $$4(au+bv)(cu+dv)=acu^2+(ad+bc)uv+bdv^2.$$

I failed to apply the formula to the equation because $a=3a$, $b=-3a$, $c=5$, $d=-5$, $u=(b-c)$, $v=?$

There's no value of $v$ so I tried to find other special product but it's only

$$(au+bv)(cu+dv)=acu^2+(ad+bc)uv+bdv^2$$ fit to the equation.

share|cite|improve this question
One factor's the negative of the other. You know how to square a binomial? – J. M. Jul 14 '12 at 7:42

1 Answer 1

up vote 1 down vote accepted

Hint: Let $x=3a(b-c)$ and $y=5$. Then \begin{align}[3a(b-c)+5][-3a(b-c)-5]&=(x+y)(-x-y)\\\\ &=(x+y)\cdot(-1)(x+y)\\\\ &=-(x+y)^2\\\\ &=-x^2-2xy-y^2. \end{align}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.